SISTEM INFORMASI GEOGRAFIS PEMETAAN BENCANA ALAM DI PROVINSI SULAWESI TENGAH - Nur, Sri Khaerawati; Sukardi; Maitano, Kevin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Natural disaster is an event related to natural phenomena that causes damage to a location on a small to large scale. According to data from the National Disaster Management Agency (BNPB), the number of disasters that occurred in Central Sulawesi in 2016–2020 totaled 251 cases. Determining the location of natural disasters will be one of the factors to facilitate government access in solving problems. Until now, the government does not have a Geographic Information System (GIS) in the form of mapping the location points of natural disasters that have occurred. Based on the problems above, a website-based information system was created, namely "Geographical Information System for Mapping the Central Sulawesi Natural Disaster. The aim is to provide information to the public, so that it can facilitate agencies in distributing information to the public in finding disaster information. Based on the results of the analysis using GIS using a questionnaire, the average results of the two variables were obtained, with an assessment of the first variable of 81.8% and the second variable of 89.4%. The average value of the two variables leads to a very good opinion,